2020
DOI: 10.1109/access.2019.2963049
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Scheduling of Non-Critical Patients Admission for Emergency Department

Abstract: The combination of the progressive growth of an aging population, increased life expectancy and a greater number of chronic diseases all contribute significantly to the growing demand for emergency medical care, and thus, causing saturation in Emergency Departments (EDs). This saturation is usually due to the admission of non-urgent patients, who constitute a high percentage of patients in an ED. The Agentbased Model (ABM) is one of the most important tools that helps to study complex systems and explores the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Hoy en día incluso existen programas basados en inteligencia artificial que permiten la gestión para una adecuada identificación de pacientes críticos y no críticos que pretendan acceder al servicio de emergencia, de esta manera se priorizaría a los adultos que presenten un estado de descompensación donde estos también estarían incluidos en el análisis de la sintomatología que presenta y sea una adecuada selección, la aplicación de dicho sistema permite una adecuada gestión de las herramientas tecnologías en los servicios críticos (6).…”
Section: Introductionunclassified
“…Hoy en día incluso existen programas basados en inteligencia artificial que permiten la gestión para una adecuada identificación de pacientes críticos y no críticos que pretendan acceder al servicio de emergencia, de esta manera se priorizaría a los adultos que presenten un estado de descompensación donde estos también estarían incluidos en el análisis de la sintomatología que presenta y sea una adecuada selección, la aplicación de dicho sistema permite una adecuada gestión de las herramientas tecnologías en los servicios críticos (6).…”
Section: Introductionunclassified
“…Resource management inside the ED can be either static or dynamic [4], [5], [6]. The first category is characterised from simple resource-allocating procedures where the constantly changing runtime environment is ignored.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Spanish triage system, ED visits are divided into five acuity levels (based on patients' clinical condition) in order to determine the priority of treatments and/or optimize the use of physical resources in an ED [2]. statistical analysis of real data set (Collect from Parc Tauli Hospital) consistent with another study [3], however, has reported that ∼ 70% of patients visiting ED are not in an urgent clinical condition and can be considered as outpatients. Use of ED services for non-urgent medical care leads to hospital overcrowding, high medical expenses, delays in clinical service delivery, and a low service efficiency for urgent patients who truly need emergency care.…”
Section: Introductionmentioning
confidence: 99%